2014
DOI: 10.1158/1078-0432.ccr-13-1777
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I Safety, Pharmacokinetic, and Pharmacodynamic Study of SAR245408 (XL147), an Oral Pan-Class I PI3K Inhibitor, in Patients with Advanced Solid Tumors

Abstract: Purpose: SAR245408 is a pan-class I phosphoinositide 3-kinase (PI3K) inhibitor. This phase I study determined the maximum tolerated dose (MTD) of two dosing schedules [first 21 days of a 28-day period (21/7) and continuous once-daily dosing (CDD)], pharmacokinetic and pharmacodynamic profiles, and preliminary efficacy.Experimental Design: Patients with refractory advanced solid malignancies were treated with SAR245408 using a 3 þ 3 design. Pharmacokinetic parameters were determined after single and repeated do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 28 publications
(39 reference statements)
12
104
0
Order By: Relevance
“…In a single-agent phase I study, robust pharmacodynamic activity across diverse tumors was evident regardless of mutational status. For example, PI3K pathway inhibition was roughly comparable in a tongue squamous cell carcinoma harboring a PIK3CA E545K mutation with that seen in tumors lacking detectable PI3K pathway alterations (24). Moreover, in that study, a partial response was evident in a patient with non-small cell lung cancer, although no mutations affecting the PI3K pathway were detected in archival tumor tissue from the patient (24).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In a single-agent phase I study, robust pharmacodynamic activity across diverse tumors was evident regardless of mutational status. For example, PI3K pathway inhibition was roughly comparable in a tongue squamous cell carcinoma harboring a PIK3CA E545K mutation with that seen in tumors lacking detectable PI3K pathway alterations (24). Moreover, in that study, a partial response was evident in a patient with non-small cell lung cancer, although no mutations affecting the PI3K pathway were detected in archival tumor tissue from the patient (24).…”
Section: Discussionmentioning
confidence: 70%
“…For example, PI3K pathway inhibition was roughly comparable in a tongue squamous cell carcinoma harboring a PIK3CA E545K mutation with that seen in tumors lacking detectable PI3K pathway alterations (24). Moreover, in that study, a partial response was evident in a patient with non-small cell lung cancer, although no mutations affecting the PI3K pathway were detected in archival tumor tissue from the patient (24). It is also not yet clear whether the presence of PIK3CA mutations or PTEN deficiency will be predictive of greater clinical responsiveness to PI3K pathway inhibitors in general, although an analysis based on combining the results of multiple early-stage trials suggested that PIK3CA H1047R mutations are associated with response (25).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As illustrated in Table 1, PD endpoints may include assessments of protein phosphorylation markers, measures of cellular proliferation/apoptosis, cell-cycle regulation biomarkers, and epigenetic changes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Serial Tumor Biopsiesmentioning
confidence: 99%
“…63 This molecule has shown good pharmacokinetic properties in animals and humans and is currently in Phase II trials for metastatic estrogen receptor (ER)-positive breast cancer and non-small cell lung cancer. Another agent derived from the heterocyclic compound quinoxalin (benzopyrazine) is XL147, 64 which is being tested in combination with other therapies including chemotherapy and targeted agents such as erlotinib and trastuzumab.…”
Section: Genomic Alterations In the Pathwaymentioning
confidence: 99%